2021
DOI: 10.3389/fimmu.2021.668113
|View full text |Cite
|
Sign up to set email alerts
|

Independent Associations of Tumor Necrosis Factor-Alpha and Interleukin-1 Beta With Radiographic Emphysema in People Living With HIV

Abstract: BackgroundPeople living with HIV (PLWH) have increased systemic inflammation, and inflammation has been suggested to contribute to the pathogenesis of emphysema. We investigated whether elevated cytokine concentrations (interleukin (IL)-1β, IL-1 receptor antagonist (IL-1RA), IL-2, IL-4, IL-6, IL-10, IL-17A, tumor necrosis factor-alpha (TNFα), interferon-gamma (IFNγ), soluble CD14 (sCD14) and sCD163 were independently associated with radiographic emphysema in PLWH.MethodsWe included PLWH from the Copenhagen Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Plasma samples were collected and stored at −80°C until use. Interleukin 6 (IL-6) was measured by enzyme immunoassays and ImP by liquid chromatography-tandem mass spectrometry, as previously described ( https://bevital.no ) [ 14 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Plasma samples were collected and stored at −80°C until use. Interleukin 6 (IL-6) was measured by enzyme immunoassays and ImP by liquid chromatography-tandem mass spectrometry, as previously described ( https://bevital.no ) [ 14 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…For analyses of inflammatory markers, plasma samples were collected at baseline and stored at À80 8C until use. The methods used for analyses of IL-1b, IL-1Ra, IL-2, IL-6, IL-10, soluble CD14, soluble CD163 and TNF-a have been described in detail elsewhere [18,21,22]. All analyses were done according to the manufacturer's instructions.…”
Section: Coronary Computed Tomography Angiography Analysismentioning
confidence: 99%
“… 190 In addition, Leung et al found that people with low DLco and a combination of centrilobular and paraseptal emphysema were more likely to have progression of emphysema, 191 and significant emphysema burden was associated with increased mortality. 192 Elevated TNFα and IL-1β, soluble CD14, nadir CD4, and low CD4/CD8 ratio are also independently associated with emphysema in PWH, 140 , 193 , 194 although reports of a direct association of HIV with emphysema are contradictory. 194 , 195 While the exact mechanisms are an area of active investigation, HIV-mediated chronic inflammation and immune dysregulation likely play an important role in emphysema formation.…”
Section: Diagnosis and Clinical Findings Of Copd In Pwhmentioning
confidence: 99%